Unravelling Stratified Microbial Assemblages in Australia’s Only Deep Anchialine System, The Bundera Sinkhole - Elbourne, Liam D. H.; Sutcliffe, Brodie; Humphreys, William; Focardi, Amaranta; Saccò, Mattia; Campbell, Matthew A.; Paulsen, Ian T.; Tetu, Sasha G. (Frontiers in Marine Science, 2022)
Bundera sinkhole, located in north-western Australia, is the only known continental anchialine system in the Southern Hemisphere. Anchialine environments are characterised by stratified water columns with complex physicochemical profiles spanning hypoxic and anoxic regions, often displaying high levels of endemism. Research on these systems has focused on eukaryotic fauna, however interest in the microbial diversity of these environments is growing, enabled by next-generation DNA sequencing. Here we report detailed analyses of the microbial communities across a depth profile within Bundera sinkhole (from 2 to 28 m), involving parallel physicochemical measurements, cell population counts and 16S rRNA amplicon analyses. We observed clear shifts in microbial cell counts, community diversity, structure and membership across the depth profile, reflecting changing levels of light, organic and inorganic energy sources as well as shifts in pH and salinity. While Proteobacteria were the most abundant phylum found, there was a high degree of taxonomic novelty within these microbial communities, with 13,028 unique amplicon sequence variants (ASVs) identified, belonging to 67 identifiable bacterial and archaeal phyla. Of these ~4,600, more than one third of the total, were unclassified below family level. A small number of ASVs were highly abundant at select depths, all of which were part of the set not classified below family level. The 2 m and 6 m samples had in common two highly abundant ASVs, belonging to the Ectothiorhodospiraceae and Thiotrichaceae families, while the 8 m community contained a single predominant ASV belonging to family Thioglobaceae. At lower depths a different Ectothiorhodospiraceae ASV comprised up to 68% relative abundance, peaking at 26 and 28 m. Canonical correspondence analyses indicated that community structure was strongly influenced by differences in key physicochemical parameters, particularly salinity, dissolved organic and inorganic carbon, phosphate and sulphate concentrations. This work highlights the potential for anchialine systems to house considerable microbial novelty, potentially driven by adaptations to the specific physicochemical makeup of their local environment. As only a small number of anchialine systems have been examined via microbial community studies to date, this work is particularly valuable, contributing new insight regarding the microbial residents of these important and sensitive environments.